Separation of energy scales in the kagome antiferromagnet TmAgGe: A magnetic-field-orientation study up to 55 T - Goddard, P; Singleton, J; Sharma, A; Morosan, E; Blundell, S; Bud'ko, S; Canfield, P (2007)
TmAgGe is an antiferromagnet in which the spins are confined to distorted kagome-like planes at low temperatures. We report angle-dependent measurements of the magnetization M in fields of up to 55 T that show that there are two distinct and separate energy scales present in TmAgGe, each responsible for a set of step-like metamagnetic transitions: weak exchange interactions and strong crystalline-electric-field (CEF) interactions. Simulations of M using a three-dimensional, free-energy minimization technique allow us to specify the physical origin of the metamagnetic transitions in low, in-plane fields. We also show that the transitions observed with the field perpendicular to the kagome planes are associated with the CEF-split multiplet of Tm. © 2007 The American Physical Society.